Prospective study of physical activity and the risk of symptomatic diverticular disease in men. Issue 2 (February 1995) - Aldoori, W H; Giovannucci, E L; Rimm, E B; Ascherio, A; Stampfer, M J; Colditz, G A; Wing, A L; Trichopoulos, D V; Willett, W C
Abstract : The relationship between physical activity and risk of symptomatic diverticular disease has not been investigated directly. This association was examined in a prospective cohort of 47, 678 American men, 40 to 75 years of age, and free of diagnosed diverticular disease, colon or rectal polyp, ulcerative colitis, and cancer before 1988. During four years of follow up, 382 newly diagnosed cases of symptomatic diverticular disease were documented. After adjustment for age, energy adjusted dietary fibre, and energy adjusted total fat, overall physical activity was inversely associated with the risk of symptomatic diverticular disease (for highest versus lowest extremes, relative risk (RR) = 0.63 (95% confidence interval (CI) 0.45, 0.88). Most of the inverse association was attributable to vigorous activity, for extreme categories RR = 0.60 (95% CI 0.41, 0.87). For activity that was not vigorous the RR was 0.93 (95% CI 0.67, 1.69). Several specific activities were inversely associated with the risk of diverticular disease, but jogging and running combined was the only individual activity that was statistically significant (p for trend = 0.03). For men in the lowest quintile for dietary fibre intake and total physical activity (compared with those in the opposite extreme), the RR was 2.56 (95% CI 1.36, 4.82). Physical activity, along with a high fibre diet, may be an important factor in the prevention of symptomatic diverticular disease.